1989
DOI: 10.1177/109019818901600107
|View full text |Cite
|
Sign up to set email alerts
|

A Hospital-Based Infant Safety Seat Program for Low-Income Families: Assessment of Population Needs and Provider Practices

Abstract: Evaluation of a hospital-based car safety seat education and loan program for low-income families included hospital interviews with new mothers (N = 94), a survey of pediatricians (N = 28), and a task analysis of the program coordinator's time. Mothers who entered the hospital with safety seats were more likely than those without safety seats to (1) be White or Mexican-American than Black; (2) not be dependent on public transportation; (3) have an older child who always rides in a car seat; and (4) wear seat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…1 In addition, black subjects of all ages are at increased risk of morbidity and death attributable to motor vehicle crashes, 2-4 presumably because of low rates of restraint use. [5][6][7][8][9][10] Although any restraint use is better than no restraint use, 11,12 the best protection for child passengers is a safety restraint that is appropriate for the age and body size of the child. Studies have demonstrated that appropriate restraint of children includes the use of belt-positioning booster seats for children 4 to 8 years of age who are too big to use forwardfacing car seats with internal harnesses but too small for lap and shoulder belts to fit appropriately.…”
mentioning
confidence: 99%
“…1 In addition, black subjects of all ages are at increased risk of morbidity and death attributable to motor vehicle crashes, 2-4 presumably because of low rates of restraint use. [5][6][7][8][9][10] Although any restraint use is better than no restraint use, 11,12 the best protection for child passengers is a safety restraint that is appropriate for the age and body size of the child. Studies have demonstrated that appropriate restraint of children includes the use of belt-positioning booster seats for children 4 to 8 years of age who are too big to use forwardfacing car seats with internal harnesses but too small for lap and shoulder belts to fit appropriately.…”
mentioning
confidence: 99%